The chylomicron saga: time to focus on postprandial metabolism - Gugliucci, Alejandro (Frontiers in Endocrinology, 2024)
Since statins have had such tremendous therapeutic success over the last three decades, the field of atherosclerosis has become somewhat LDL-centric, dismissing the relevance of triglycerides (TG), particularly chylomicrons, in atherogenesis. Nonetheless, 50% of patients who take statins are at risk of developing atherosclerotic cardiovascular disease (ASCVD) and are unable to achieve their goal LDL-C levels. This residual risk is mediated, in part by triglyceride rich lipoproteins (TRL) and their remnants. Following his seminal investigation on the subject, Zilversmit proposed that atherosclerosis is a postprandial event in 1979 (1-4). In essence, the concept suggests that remnant cholesterol-rich chylomicron (CM) and very-low density lipoprotein (VLDL) particles play a role in atherogenesis. Given the foregoing, this narrative review addresses the most recent improvements in our understanding of postprandial dyslipidemia. The primary metabolic pathways of chylomicrons are discussed, emphasizing the critical physiological role of lipoprotein lipase and apoCIII, the importance of these particles' fluxes in the postprandial period, their catabolic rate, the complexities of testing postprandial metabolism, and the role of angiopoietin-like proteins in the partition of CM during the fed cycle. The narrative is rounded out by the dysregulation of postprandial lipid metabolism in insulin resistance states and consequent CVD risk, the clinical evaluation of postprandial dyslipidemia, current research limits, and potential future study directions. immunological and lipid abnormalities.